Association of concomitant continuous pain in trigeminal neuralgia with a narrow foramen ovale - Li, Shuo; Liao, Chenlong; Yang, Xiaosheng; Zhang, Wenchuan (Frontiers in Neurology, 2023)
Background The pathogenesis of concomitant continuous pain remains unclear and is worthy of further study. In this clinical study, we aimed to explore the potential role of a narrow foramen ovale in the development of concomitant continuous pain. Methods A total of 108 patients with classical trigeminal neuralgia affecting the third branch of the trigeminal nerve and 46 healthy individuals were enrolled in this study. Three-dimensional reconstructed computerized tomography images of all participants were collected, and the morphometric features of the foramen ovale were examined by two investigators who were blinded to the clinical data of the patients. Results In this cohort, patients with concomitant continuous pain suffered from more sensory abnormalities (18.4% vs. 2.9%, p = 0.015) and responded more poorly to medication (74.3% vs. 91.9%, p = 0.018) than patients without concomitant continuous pain. While no significant differences regarding the mean length (5.02 mm vs. 5.36 mm, p > 0.05) and area (22.14 mm2 vs. 23.80 mm2, p > 0.05) were observed between patients with and without concomitant continuous pain, the mean width of the foramen ovale on the affected side in patients with concomitant continuous pain was significantly narrower than that in patients without concomitant continuous pain (2.01 mm vs. 2.48 mm, p = 0.003). Conclusion This neuroimaging and clinical study demonstrated that the development of concomitant continuous pain was caused by the compression of the trigeminal nerve owing to a narrow foramen ovale rather than responsible vessels in classical trigeminal neuralgia.